Chemical induction of gut β-like-cells by combined FoxO1/Notch inhibition as a glucose-lowering treatment for diabetes - Takumi Kitamoto; Yun-Kyoung Lee; Nishat Sultana; Hitoshi Watanabe; Wendy M. McKimpson; Wen Du; Jason Fan; Bryan Diaz; Hua V. Lin; Rudolph L. Leibel; Sandro Belvedere; Domenico Accili (Elsevier, 2022)
Objective: Lifelong insulin replacement remains the mainstay of type 1 diabetes treatment. Genetic FoxO1 ablation promotes enteroendocrine cell (EECs) conversion into glucose-responsive β-like cells. Here, we tested whether chemical FoxO1 inhibitors can generate β-like gut cells. Methods: We used Ngn3-or Villin-driven FoxO1 ablation to capture the distinctive developmental effects of FoxO1 on EEC pool. We combined FoxO1 ablation with Notch inhibition to enhance the expansion of EEC pool. We tested the ability of an orally available small molecule of FoxO1 inhibitor, Cpd10, to phenocopy genetic ablation of FoxO1. We evaluated the therapeutic impact of genetic ablation or chemical inhibition of FoxO1 on insulin-deficient diabetes in Ins2Akita/+ mice. Results: Pan-intestinal epithelial FoxO1 ablation expanded the EEC pool, induced β-like cells, and improved glucose tolerance in Ins2Akita/+ mice. This genetic effect was phenocopied by Cpd10. Cpd10 induced β-like cells that released insulin in response to glucose in gut organoids, and this effect was enhanced by the Notch inhibitor, DBZ. In Ins2Akita/+ mice, a five-day course of either Cpd10 or DBZ induced intestinal insulin-immunoreactive β-like cells, lowered glycemia, and increased plasma insulin levels without apparent adverse effects. Conclusion: These results provide proof of principle of gut cell conversion into β-like cells by a small molecule FoxO1 inhibitor, paving the way for clinical applications.